2018
DOI: 10.1002/adhm.201700994
|View full text |Cite
|
Sign up to set email alerts
|

Skin Conformal Polymer Electrodes for Clinical ECG and EEG Recordings

Abstract: Preparation-free and skin compliant biopotential electrodes with high recording quality enable wearables for future healthcare and the Internet of Humans. Here, super-soft and self-adhesive electrodes are presented for use on dry and hairy skin without skin preparation or attachment pressure. The electrodes show a skin-contact impedance of 50 kΩ cm at 10 Hz that is comparable to clinical standard gel electrodes and lower than existing dry electrodes. Microstructured electrodes inspired by grasshopper feet adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
182
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(184 citation statements)
references
References 18 publications
0
182
0
2
Order By: Relevance
“…Various devices incorporating biologically inspired architectures have recently been demonstrated to achieve high conformity to rough, often hairy and/or wet (e.g., perspiration, oil, and blood) surfaces of human interfaces for long‐term signaling. The architectures include gecko‐inspired nanohairs, insect pad‐like microfibrillars, frog pad‐inspired microchannels, and octopus sucker‐like microcavities . Pang et al reported a flexible pressure sensor with a microhairy interface to demonstrate signal amplification and measurements of the weak jugular venous pulses (JVPs) from a wireless transmitter .…”
Section: Bioelectronics With Bioinspired Adhesive Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various devices incorporating biologically inspired architectures have recently been demonstrated to achieve high conformity to rough, often hairy and/or wet (e.g., perspiration, oil, and blood) surfaces of human interfaces for long‐term signaling. The architectures include gecko‐inspired nanohairs, insect pad‐like microfibrillars, frog pad‐inspired microchannels, and octopus sucker‐like microcavities . Pang et al reported a flexible pressure sensor with a microhairy interface to demonstrate signal amplification and measurements of the weak jugular venous pulses (JVPs) from a wireless transmitter .…”
Section: Bioelectronics With Bioinspired Adhesive Architecturesmentioning
confidence: 99%
“…While bioelectronics with microstructures have been used to increase detection of signal magnitudes by high conformity, diagnostic devices with bioinspired architectures for adhesion to skin have also drawn much attention. Patch‐type sensors with bioinspired dry adhesive architectures provide not only repetitive and long‐term attachment, but also stability for biosignal monitoring without conventional acrylic‐based glues or surgical suture . Kim et al proposed stretchable and conductive adhesives with mushroom‐shaped architectures to demonstrate cost‐effective and reusable all‐in‐one devices for biosignal measurements under active motions (i.e., moving, wrist‐curling, and writing) .…”
Section: Bioelectronics With Bioinspired Adhesive Architecturesmentioning
confidence: 99%
“…Attributed to their excellent mechanical compliance, they could form fully conformal contact with the human epidermis, resulting not only in enhanced sensitivity but also in an unprecedented level of comfort regarding wearable devices . As a type of epidermal device, the conformal epidermal electrodes have been widely utilized for biometric sensing . Lu and coworkers reported a graphene‐based tattoo‐like epidermal electrode, which could be used to measure various physiological signals .…”
mentioning
confidence: 99%
“…It has the potential to replace conventional sampling from blood in a minimally invasive manner by using microneedles or iontophoresis electrodes. [129] These sensors are able to detect ionic electrophysiological signals of the human body and convert these ionic signals to processable electronic signals. [123] Continuous monitoring of ionized calcium and pH of sweat using a wearable sensor provides essential information on human metabolism and minerals homeostasis.…”
Section: Wearable Devicesmentioning
confidence: 99%
“…[123] Continuous monitoring of ionized calcium and pH of sweat using a wearable sensor provides essential information on human metabolism and minerals homeostasis. [129,131] Devices that monitor glucose levels from sweat and use this information to trigger insulin release are available for diabetic patients. Tumor-related biomarkers are also recently found in tear which can be used to predict breast cancer.…”
Section: Wearable Devicesmentioning
confidence: 99%